Transcranial high-intensity Magnetic Resonance-guided focused ultrasound (tcMRgFUS) – safety and impacts on tremor severity and quality of life. (July 2022) - Purrer, Veronika; Borger, Valeri; Pohl, Emily; Upadhyay, Neeraj; Boecker, Henning; Schmeel, Carsten; Pieper, Claus Christian; Wüllner, Ullrich
Abstract: Introduction: Transcranial high-intensity Magnetic Resonance-guided Focused Ultrasound (tcMRgFUS) is a technique for treatment of severe, medication-refractory Essential Tremor (ET). We summarize 1-year follow-up results focusing on clinical and safety parameters and impacts on quality of life. Methods: A total of 45 patients with severe, medication-refractory ET were treated with tcMRgFUS thalamotomy. 37 patients completed the clinical follow-up of 12 months. Tremor severity, disability and quality of life were measured using the Clinical Rating Scale for Tremor (CRST), surface electromyography, the Quality of Life in Essential Tremor Questionnaire (QUEST) and the Short-Form-36 questionnaire (SF-36). Depressive symptoms and cognitive function were assessed using standardized questionnaires. Electrophysiological measurements were conducted to evaluate possible effects on central motor and sensory pathways. Results: 1 year after tcMRgFUS the mean tremor improvement on a hand-specific subscore of the CRST was 82%. The QUEST and SF-36 revealed an improvement of mental quality of life, especially in activities of daily living and psychosocial function; depressive symptoms decreased significantly. There was no worsening of cognitive function overt within the self-rating questionnaire; no prolongation of sensory evoked potentials or central motor conduction time occurred. Side effects were mostly classified as mild (78%) and transient (62%). Conclusions: TcMRgFUS for severe tremor has a distinct impact on quality of life and neuropsychological symptoms. Self-assessments of cognitive function revealed stable outcomes 1 year after tcMRgFUS. No prolongation of sensory or motor conduction time were found in neurophysiology measures. Side effects occurred in 78% of treated patients but were mostly transient and mild. Highlights: TcMRgFUS may develop into an alternative treatment option for therapy-refractory essential tremor. Tremor in the treated extremity improved up to 82% 1 year after tcMRgFUS, which had a significant impact on quality of life. Using a validated self-rating questionnaire, no decline of cognitive function was reported 1 year after tcMRgFUS. Side effects occurred in 78% of the patients, of which 78% were classified as mild. 62% of all side effects were transient. Delayed side effects, such as taste disturbances and mostly transient involuntary movements may occur in tcMRgFUS.